PEMBERDAYAAN BUDAYA LITERASI MELALUI PEMBUATAN POJOK BACA DI SDN 242 DI DESA SINAR GADING - Eza Rejeki; Muhammad Jainnuri (AbdiMasya | Hira Institute, 2024)
It is hoped that the use of classroom reading corners can foster reading habits. Educational institutions are trying to create reading corners as a use for classroom corners. Reading corners can enable students to carry out reading activities that can explore and train their potential. Literacy is an ability that must be mastered in searching for information, literacy is a very broad meaning, not just about writing and reading, financial literacy, reading-writing literacy, digital literacy and other literacies. with literacy skills a person can do very well. The type of research used in this research is descriptive literature writing methods and data collection using observation, interviews and documentation techniques. Descriptive research is research that aims to collect information about an existing symptom, namely the state of the problem that existed at the time the research was carried out. Apart from collecting data using observation, interviews and documentation techniques, sources can also be obtained from primary and secondary data. Primary data is data taken from the first data, namely coordinating with the school principal to request permission to establish a reading corner. After that, coordinate with the teachers or teaching staff at the school. Secondary data is data taken from other literature such as books, journals. The corner program uses the creation of reading corners in schools which is implemented so that students are interested in improving their literacy skills. When carrying out the implementation, students were enthusiastic about this literacy.